Pengaruh Cooperative Learning Terhadap Resiliensi Akademik Remaja - Laura, Anastasia; Nugroho, Andrea Dean; Wulandari, Angelina Arum; Wibisono, Arya Brillianto; Budiman, Daniel Thaddeus (Psychopreneur Journal, 2022)
Academic resilience is a person's ability to maintain academic achievements even under the presence of academic pressure. Due to experiencing the storm and stress phase, adolescents may feel depressed over academic problems and be prone to stress, depression, and even suicide. The aim of this research was to discover the effectiveness of cooperative learning method to increase academic resilience in adolescents' learning process. This research used a quasi-experiment method with one-group pretest- posttest design. Purposive sampling was used as the participant sampling technique. The participants are 14 adolescents at the age of 12 to 17 years old who are under the management of WVI (World Vision Indonesia). ARS-30 scale (Academic Resilience Scale) was used to collect participants’ academic resilience data. The result of this research showed that cooperative learning method is not significant to increase academic resilience with p=0,475 (p>0,05).